Typhonium trilobatum Demonstrates Both Antioxidant and Acetylcholinesterase Inhibitory Activities In vitro (Bangladesh Pharmaceutical Journal, 2019)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder of the elderly people. Cholinergic dysfunction and oxidative stress have been found to be related with the development of the disease. Typhonium trilobatum L. Scott has been used traditionally in folk medicine as a central nervous system stimulant. In this study, we have investigated the various extracts of T. trilobatum for acetylcholinesterase and antioxidant activities in vitro. All the tested extracts exhibited inhibition against acetylcholinesterase. Petroleum ether extract exhibited the highest inhibition with an IC50 of 255.26 g/ml. Likewise all the extracts were found to possess antioxidant activity. In reducing power assay, petroleum ether extract showed the highest reducing power with an absorbance of 0.874 at 0.1 mg/ml concentration and in DPPH radical scavenging assay, chloroform extract exhibited the highest scavenging activity with an IC50 of 619.54 µg/ml. Phytochemical analyses of the four extracts revealed that the ethyl acetate extract contained the highest amount of flavonoids and petroleum ether had the highest amount of phenolics. These results suggest that T. trilobatum has both antioxidant and cholinesterase inhibitory activities, which may be useful in reducing the risk of AD.Bangladesh Pharmaceutical Journal 22(1): 92-98, 2019